2012
DOI: 10.1159/000337300
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Extreme Phenotype Sequencing Design for Discovering and Testing Common and Rare Genetic Variants: Efficiency and Power

Abstract: Next-generation sequencing technology provides an unprecedented opportunity to identify rare susceptibility variants. It is not yet financially feasible to perform whole-genome sequencing on a large number of subjects, and a two-stage design has been advocated to be a practical option. In stage I, variants are discovered by sequencing the whole genomes of a small number of carefully selected individuals. In stage II, the discovered variants of a large number of individuals are genotyped to assess associations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…Under the extreme phenotype hypothesis, one approach to reduce the amount of sequencing required is to sequence only individuals in the upper and lower tails of a phenotypic distribution 8486 . For example, the therapeutic dose of a particular drug may vary tenfold between the 5% of patients that are most sensitive and the 5% of patients that are most resistant: both of these sets of patients may be enriched for the genetic variants that contribute to differences in drug sensitivity 87 .…”
Section: Alternatives To Clinical Gwassmentioning
confidence: 99%
“…Under the extreme phenotype hypothesis, one approach to reduce the amount of sequencing required is to sequence only individuals in the upper and lower tails of a phenotypic distribution 8486 . For example, the therapeutic dose of a particular drug may vary tenfold between the 5% of patients that are most sensitive and the 5% of patients that are most resistant: both of these sets of patients may be enriched for the genetic variants that contribute to differences in drug sensitivity 87 .…”
Section: Alternatives To Clinical Gwassmentioning
confidence: 99%
“…Rare variants, with minor allele frequencies (MAFs) of less than 0.01, and with modest to high effect sizes [57], might play a crucial role in the etiology of complex traits and could account for missing heritability unexplained by common variants.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that extreme sampling can enrich for the presence of causal variants 16,17 and, furthermore, that extreme phenotypic sampling and/or a twostage analysis can lead to gains in power. [17][18][19] Lee et al 20 compare available gene-based tests and discuss design strategies for RVASs. Meta-analysis frameworks have been proposed to combine individual variant score statistics across studies and reconstruct gene-based tests, 21 but this may lead to biases when selection, sequencing, and quality control differ between studies.…”
Section: Introductionmentioning
confidence: 99%